Update on the Epidemiology of coccidioidomycosis in the United States - McCotter, Orion Z. (Med Mycol, 2019)
The incidence of reported coccidioidomycosis in the past two decades has increased greatly; monitoring its changing epidemiology is essential for understanding its burden on patients and the healthcare system and for identifying opportunities for prevention and education. We provide an update on recent coccidioidomycosis trends and public health efforts nationally and in Arizona, California, and Washington State. In Arizona, enhanced surveillance shows that coccidioidomycosis continues to be associated with substantial morbidity. California reported its highest yearly number of cases ever in 2016 and has implemented interventions to reduce coccidioidomycosis in the prison population by excluding certain inmates from residing in prisons in high-risk areas. Coccidioidomycosis is emerging in Washington State, where phylogenetic analyses confirm the existence of a unique Coccidioides clade. Additional studies of the molecular epidemiology of Coccidioides will improve understanding its expanding endemic range. Ongoing public health collaborations and future research priorities are focused on characterizing geographic risk, particularly in the context of environmental change; identifying further risk reduction strategies for high-risk groups; and improving reporting of cases to public health agencies.